One-day versus four-day antibiotic treatment for acute right colonic uncomplicated diverticulitis: A randomized clinical trial - Park, Jung Ho; Park, Hyoung Chul; Lee, Bong Hwa (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Currently, right colonic uncomplicated diverticulitis is typically treated with antibiotic therapy. However, the optimal duration of treatment is unknown. The aim of the present study was to compare the treatment failure rates between 1- and 4-day antibiotic treatment protocols. Materials and Methods: A prospective randomized study in adults presenting with uncomplicated diverticulitis at the first episode from July 2011 to June 2014 was performed. Patients were randomized to receive intravenous antibiotics for 1 day (1-day group) or intravenous and oral antibiotics for 4 days (4-day group). All patients received cefmetazole and metronidazole. Treatment failure was defined as readmission within 30 days and disease recurrence during the follow-up period. Results: Overall, 87 and 89 patients were randomized to the 1-day and 4-day groups, respectively. All patients were successfully treated initially. The hospital length of stay was shorter in the 1-day group than in the 4-day group (3.1 vs. 3.8 days, respectively; p Conclusion: Single-day antibiotic treatment is as effective as 4-day therapy for the prevention of readmission and recurrence in patients with right colonic uncomplicated diverticulitis. Cite this article as: Park JH, Park HC, Lee BH. One-day versus four-day antibiotic treatment for acute right colonic uncomplicated diverticulitis: A randomized clinical trial. Turk J Gastroenterol 2019; 30(7): 605-10.